Riparian Forests of Combu Island: Biodiversity Preservation and Environmental Degradation Challenges - Silva, Nicolly Christyne Ferreira e; Xavier Júnior, Sebastião Ribeiro; Corrêa, Ayssa de Freitas; Gomes , Marcelo Trindade (Technical and Scientific Journal Green Cities, 2025)
This article analyzes the importance of riparian forests in environmental conservation on Ilha do Combu, located in the Amazon region of Brazil. Riparian forests are vital for preserving biodiversity and water quality, as well as playing essential roles in preventing erosion and protecting water resources. However, the area faces significant challenges due to degradation caused by anthropogenic activities, such as unmanaged tourism and economic exploitation. The research was conducted through a literature review, field visits, and the creation of thematic maps, allowing for an in-depth analysis of local conditions and degradation impacts. The necessity of public policies and management plans that integrate environmental conservation with sustainable development is highlighted, emphasizing the restoration of riparian forests through the planting of native species. Community involvement is crucial to ensure the effectiveness of preservation efforts, promoting sustainable use of natural resources and protecting the rich biodiversity of Ilha do Combu.